Pengaruh Store Layout dan Store Atmosphere terhadap Purchase Intention Gen Z pada Ritel Modern di Malang - Andreas Hadirianto; Santi Widyaningrum; I Gusti Ngurah Agung Arya Bhakta Narayana; Sahala Manalu; Catharina Aprilia Hellyani (JURNAL RISET MANAJEMEN (JURMA), 2026)
Modern retail competition increasingly depends on the ability of stores to create efficient, comfortable, and memorable shopping experiences for Generation Z consumers. This study aims to examine the effects of Store Layout and Store Atmosphere on Purchase Intention in modern retail stores in Malang City. A quantitative associative design was employed using survey data from 123 Generation Z respondents selected through purposive sampling. The data were analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression with IBM SPSS Statistics 26. The results show that Store Layout has a positive and significant effect on Purchase Intention (t = 2.051; Sig. = 0.042), and Store Atmosphere also has a positive and significant effect (t = 2.460; Sig. = 0.015). Simultaneously, both variables significantly affect Purchase Intention (F = 10.570; Sig. < 0.001), although the adjusted coefficient of determination is modest (Adjusted R2 = 0.136). The findings imply that retailers should integrate functional layout design with sensory atmosphere management to strengthen Generation Z consumers’ intention to purchase.